Schiff base complexes with different metals incorporating derivatives of 3, 6‐di‐tert‐butylcarbazole. (5th January 2021) - Gruzdev, Matvey S.; Chervonova, Ulyana V.; Ksenofontov, Alexander A.; Krestianinov, Mikhail A.; Alexandrov, Anatoly I.; Pashkova, Tamara V.
Abstract : Four new mononuclear complexes formed by the asymmetric azomethine ligand have been synthesized and characterized. Fe (III), Ga (III), Cu (II), and Co (II) ions were used as a central metal ion. The chelating ligand contains derivatives of 3, 6‐di‐ tert ‐butylcarbazole as a chromophor. The data of far FT‐IR spectroscopy and mass spectrometry confirmed the formation of HCN bond and the coordination of metal ion through deprotonated oxygen and azomethine nitrogen. The X‐ray powder analysis of polycrystalline complexes showed that the crystal cells of all complexes are triclinic, with unit cells containing four molecules each. The counter‐ions are regularly embedded into the crystalline lattice. The conformation of the molecules of all complexes is elongated and symmetric. The thermal gravimetric analysis showed a high stability of all complexes above 200°C. The UV–Vis and fluorescence spectral data of the synthesized compounds were obtained in acetone, benzene, dichloromethane, chloroform, DMA, DMF, DMSO, and THF. The complexes show intensive π–π*, n –π*, and charge‐transfer (CT) bands in the range from 200 to 400 nm in all solvents, whereas the ligand shows intensive π–π*, n –π* bands only. A strong red shift (21–31 nm) of the emission band maximum of the complexes is observed upon transition from nonpolar to polar solvents. Abstract : Four new mononuclear complexes formed by the asymmetric azomethine ligand have been synthesized and characterized. Fe (III), Ga (III), Cu (II), and Co (II) ions were used as a central metal ion and derivatives of 3, 6‐di‐ tert ‐butylcarbazole as a chromophor. The complexes show intensive π–π*, n –π*, and charge‐transfer (CT) bands in the range from 200 to 400 nm in all solvents, whereas the ligand shows intensive π–π*, n –π* bands only. A strong red shift (21–31 nm) of the emission band maximum of the complexes is observed upon transition from nonpolar to polar solvents.